Cone-beam computed tomographic investigation of the association between impacted mandibular third molars and the development of distal caries in adjacent second molars in a Chinese population - Wenyuan Zhou; Zaidao Xiong; Juan Fan; Tao Yang; Yongchun Gu (Heliyon)
To investigate the association between impacted mandibular third molars (IMTMs) and the prevalence of distal caries in adjacent mandibular second molars (MSMs) in a Chinese population, a retrospective analysis was conducted using cone-beam computed tomography (CBCT) images obtained from routine dental practice for various diagnostic purposes. The impaction patterns of the mandibular third molars were recorded using Winter's classification and Pell and Gregory's classification. The occurrence and severity of distal caries in MSMs were also documented. Chi-square tests and logistical regression analyses were used to assess the association between distal caries in the MSM and variables. A total of 552 scans were included, and the frequency of IMTMs was 64.5 % (647/1003). According to Winter's classification, the most common type of impaction was mesioangular impaction (45.5 %), followed by horizontal (31.2 %) and vertical impaction (17.5 %). Based on Pell and Gregory's classification, level B impaction (54.9 %) and class II impaction (57.5 %) were the most frequent. Compared to the non-impaction group, the frequency of distal caries in the MSMs for the impaction group was significantly higher (19.5 % [126/647] vs. 3.5 % [12/346]; p < 0.01). The prevalence of carious lesion in MSMs associated with IMTMs increased with age, peaking in the 31–35 years age group, followed by a decrease in the 36–40 years age group, and then rising again in patients aged above 40 years. Logistical regression analyses confirmed that the pattern of IMTMs significantly associated with distal caries in MSMs, and mesioangular angulation of IMTM (OR = 11.22), position A (OR = 8.37), a type I ramus relationship (OR = 2.70), and the 18–25 age group (OR = 2.62) were identified as significant risk factors (all p < 0.01). In conclusion, the present study demonstrates that the pattern of IMTMs contributes to the development of distal caries in adjacent MSMs. Clinicians should carefully consider these factors when evaluating the need for prophylactic extraction of IMTMs to prevent distal caries in MSMs.